Systematic in vitro nanotoxicity study on anodic alumina nanotubes with engineered aspect ratio: Understanding nanotoxicity by a nanomaterial model. (April 2015) - Wang, Ye; Kaur, Gagandeep; Zysk, Aneta; Liapis, Vasilios; Hay, Shelley; Santos, Abel; Losic, Dusan; Evdokiou, Andreas
Abstract: Here, we report a detailed and systematic approach for studying the in vitro nanotoxicity study of high aspect ratio (HAR) nanomaterials using anodic alumina nanotubes (AANTs) as a nanomaterial model. AANTs with bio-inert properties and tailored aspect ratios ranging from 7.8 to 63.3 were synthesized by an electrochemical pulse anodization process. Cytotoxicity studies were conducted with RAW 264.7 mouse macrophage cells and MDA-MB 231-TXSA human breast cancer cells through several toxicity parameters, including cell viability and morphology, pro-inflammatory response, mitochondrial depolarization, lysosomal membrane permeabilization (LMP), induction of autophagy and endoplasmic reticulum (ER) stress. The resulting toxicity patterns were cell-type dependent and strongly related with AANTs dose, length of time, and importantly the AR of AANTs. Long AANTs triggered enhanced cell death, morphological changes, tumor necrosis factor α (TNF-α) release, LMP and ER stress than short AANTs. The toxic AR window of AANTs was determined to be 7.8, which is shorter than that of other previously reported HAR nanomaterials. This toxic AR window provides a promising opportunity to control the nanotoxicity of HAR nanomaterials for their advanced drug delivery application.